2020
DOI: 10.30773/pi.2019.0324
|View full text |Cite
|
Sign up to set email alerts
|

Depression and APOEε4 Status in Individuals with Subjective Cognitive Decline: A Meta-Analysis

Abstract: Objective To evaluate the associative role of depression and apolipoprotein E epsilon 4 allele (APOEε4) in subjective cognitive decline (SCD) and its progression to objective cognitive decline.Methods After literature search in electronic databases, studies were selected by following precise eligibility criteria. Meta-analyses were performed to examine the role of APOEε4 and depression in SCD or its progression to mild cognitive impairment (MCI) or dementia.Results APOEε4 positivity was not different between S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…The ε3 allele was observed in 77.8% of individuals, the ε4 allele in 13.2% and the ε2 allele in 9%. Our data are in agreement with the results of researchers from around the world [ 12 , 14 , 15 ] as well as from domestic researchers [ 4 , 35 ]. For example, 70.4% had the ε3/ε3 genotype, 9% had the ε3/ε4 genotype, and 6% had the ε2/ε3 genotype, according to I.B.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The ε3 allele was observed in 77.8% of individuals, the ε4 allele in 13.2% and the ε2 allele in 9%. Our data are in agreement with the results of researchers from around the world [ 12 , 14 , 15 ] as well as from domestic researchers [ 4 , 35 ]. For example, 70.4% had the ε3/ε3 genotype, 9% had the ε3/ε4 genotype, and 6% had the ε2/ε3 genotype, according to I.B.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have shown that certain genotypic polymorphisms in the APOE gene coding region are risk factors for depression and other diseases [ 13 , 14 ]. In 2020, Y.P.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent communitybased studies on very large populations showed that depressive symptoms increase the risk of progression to objective cognitive decline and dementia in SCD patients (89,90). A metaanalysis by Huang et al showed that depression was significantly higher in individuals with SCD than in normal individuals but there was no difference between SCD and MCI or between SCD converters and non-converters (91). In a 7-years of follow-up study of more than 13000 cognitively normal individuals over 50-years old, SCD and depression were independently associated with the risk of developing MCI or dementia but the risk was highest when both depression and SCD coexisted at baseline (90).…”
Section: Discussionmentioning
confidence: 99%
“…Filippov et al proposed genotyping of the apolipoprotein E (APOE) allele in combination with EEG to identify early-onset AD [32]. This is further supported by a meta-analysis that showed that 15-45% of APOEε4 carriers had developed AD [33]. The incidences of AD are higher in APOEε4/4 patients (25-45%) who fall into the age group of 75-80 years compared with APOEε3/4 carriers (15-25%) when matched for age [34].…”
Section: Risk Factorsmentioning
confidence: 99%